2005
DOI: 10.1002/ange.200500375
|View full text |Cite
|
Sign up to set email alerts
|

Molekülverbindungen mit Mo‐O‐Bi‐Einheiten

Abstract: Professor Manfred Meisel zum 65. Geburtstag gewidmetDie bemerkenswerte katalytische Aktivität von n MoO 3 / Bi 2 O 3 -Phasen bei der allylischen Propenoxidation (SOHIOProzess) ist seit langem Gegenstand kontroverser Diskussionen.[1] Sie könnte mit dem Vorliegen von Mo-O-Bi-Strukturelementen auf der Katalysatoroberfläche zusammenhängen, wenn man davon ausgeht, dass diese ein besonderes Potenzial für H-Atom-Abstraktionen oder Radikaleinfangreaktionen entwickeln können. Über die strukturelle Charakterisierung von… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In 6 the Hf−O bond length (1.957(3) Å) is longer than that in LAlMe(μ-O)HfMeCp 2 (1.919 Å) . The Bi−O bond length in compounds 3 − 6 (av 2.038 Å) is comparable to those observed in (BiTi 2 O(O i Pr) 9 (2.090 Å) and [(Cp* 2 MoO 3 )BiPh 3 ] (2.201 Å) but considerably shorter than that found in [{Bi(Hsal) 3 } 2 {Al(acac) 3 }] (2.765 Å) …”
Section: Resultssupporting
confidence: 64%
“…In 6 the Hf−O bond length (1.957(3) Å) is longer than that in LAlMe(μ-O)HfMeCp 2 (1.919 Å) . The Bi−O bond length in compounds 3 − 6 (av 2.038 Å) is comparable to those observed in (BiTi 2 O(O i Pr) 9 (2.090 Å) and [(Cp* 2 MoO 3 )BiPh 3 ] (2.201 Å) but considerably shorter than that found in [{Bi(Hsal) 3 } 2 {Al(acac) 3 }] (2.765 Å) …”
Section: Resultssupporting
confidence: 64%
“…With the background of the oxidation of propene to acrolein, which can be catalyzed by mixed metal oxides n MoO 3 /Bi 2 O 3 , , we and others have developed routes to compounds with Mo−O−Bi units , and with Mo−Bi metal bonds. We found that Mo−Bi bonds can be created by reactions of molybdocene dihydrides with bismuth alkoxides or siloxides. ,,, It was also shown that replacement of the bismuth alkoxides in such reactions by tin and antimony halides results in complexes with Mo−Sn and Mo−Sb bonds . We were interested in investigating whether also the molybdocene dihydride component can be exchanged by other transition metal hydrides in reactions with bismuth alkoxides and in how far the “hydride-alkoxide” route thus might represent a more general procedure to access transition metal−bismuth systems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have been interested in molecular heterobimetallic oxo compounds that can mimic certain structural units proposed to occur on the surfaces of corresponding heterogeneous catalysts composed of two metal oxide components. [16][17][18][19][20][21][22] The fact that MoO 3 /Fe 2 O 3 catalysts are employed for the oxidation of methanol to formaldehyde in the so-called FORMOX process has spurred us to investigate Fe-O-Mo compounds. While some purely inorganic polyoxometal aggregates [23][24][25][26][27][28][29][30] and coordination polymers [30][31][32][33][34][35][36][37] featuring Fe-O-Mo entities have been published, so far only five structurally characterised molecular coordination compounds have been reported, where molybdate units are bridging ligated iron ions.…”
Section: Resultsmentioning
confidence: 99%